Integrating search methods on Active Documents - Soares Xavier, Maria Ester (2003)
In this work we present an extension of the parametric network representation language used by Active Documents models. The extension incorporates a new kind of parameter to the representation language. This new kind of parameter enables the reuse of a task-especific library of problem solving components implementing automatic search in Active Documents Systems. In order to illustrate the use of this new parameter, the Hill Climbing, Propose and Backtracking, Complete the Model Then Revise and Extend The Model Then Revise methods were implemented. These methods were used for solving an office allocation problem. The knowledge modeling technique used here allows the knowledge engineer to configure new methods using the library components. The knowledge engineer can also include new components to the library